IMPROVING THE STUDENTS’ READING COMPREHENSION ACHIEVEMENT IN DESCRIPTIVE TEXT BY USING INDEX CARD MATCH STRATEGY - Septiwi Hadi Lubis; Elia Masa Gintings (Universitas Negeri Medan, 2014)
This study deals with improving students’ reading comprehension by using Index Card Match strategy. This study was conducted by using classroom action research. The subject of the research was class VIIa MTs.Lab. IKIP Al- Washliyah Medan which consisted of 36 students. The research was conducted in two cycles and every cycle consists of four meetings and two meetings. The instruments for collecting data were multiple choice tests as the quantitative data and observation sheet, questionnaire sheet and diary notes as the qualitative data. Based on multiple choice test score, students’ score kept improving in every test. In test I, the mean score was 63.05, in test II, the mean score was 67.63, and in test III the mean score was 72.77. The finding of the study indicated that the implementation of Index card Match strategy was successful since the criteria of success were achieved. The result of observation sheet and questionnaire sheet showed that students were active involved in the classroom. Based on the finding before, it’s concluded that Index Card Match strategy could improve students’ reading comprehension.